2004
DOI: 10.1002/lsm.20108
|View full text |Cite
|
Sign up to set email alerts
|

Low level laser irradiation stimulates mitochondrial membrane potential and disperses subnuclear promyelocytic leukemia protein

Abstract: These changes reflect a biostimulative boost that causes a shift of the cell from a quiescent to an activated stage in the cell cycle heralding proliferation and suppression of inflammation. Further characterization of MMP kinetics may provide a quantitative basis for assessment of the effect of LLLI in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 30 publications
3
61
0
7
Order By: Relevance
“…It should be noted that the positive LLLI effect applied not only to ovulation, but also to fertilization and early embryonic development, because in the TG, a larger number of oocytes were fertilized and more embryos recovered in comparison with the CG. Gavish et al (2004) reported that photons from the laser irradiation are absorbed by proteins of the mitochondrial respiratory chain that convert this energy into chemical energy. They also described that in isolated mitochondria, the LLLI increased the mitochondrial membrane potential, the proton gradient, and the rate of ADP/ATP replacement.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the positive LLLI effect applied not only to ovulation, but also to fertilization and early embryonic development, because in the TG, a larger number of oocytes were fertilized and more embryos recovered in comparison with the CG. Gavish et al (2004) reported that photons from the laser irradiation are absorbed by proteins of the mitochondrial respiratory chain that convert this energy into chemical energy. They also described that in isolated mitochondria, the LLLI increased the mitochondrial membrane potential, the proton gradient, and the rate of ADP/ATP replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Porém, devido ao fato dos grupos controle não terem apresentado qualquer sinal de apoptose, estes valores tornaram-se estatisticamente significantes, mesmo sendo extremamente inferiores aos seus 77 controles positivos. De outra forma, deve-se lembrar que após a estimulação das mitocôndrias ter sido atingida com a luz laser, a atividade mitocondrial retorna aos níveis normais, a não ser que outra estimulação com LLLT seja entregue às células (192) .…”
Section: Discussionunclassified
“…Diversos trabalhos mostram que a estimulação com laser leva a um aumento muito relevante dos níveis mitocondriais, em torno de 150% (192,263,264,294) . Estes níveis voltam ao normal após aproximadamente uma hora, no entanto, e continuam decaindo até atingir 50% da atividade mitocondrial do grupo controle durante as próximas duas horas (192) .…”
Section: Discussionunclassified
See 2 more Smart Citations